Establishment of Food Plots for White-tailed Deer in Central and South Florida - Emma V. Willcox; Brandon J. Schad; William M. Giuliano; James F. Selph (EDIS, 2007)
WEC-223, a 7-page fact sheet by Emma. V. Willcox, Brandon J. Schad, William M. Giuliano, and James F. Selph, describes how and why to add food plots to habitats being managed for white-tailed deer. It discusses considerations for location, size, shape and distribution; what to plant; how to plant, fertilize, and lime the plot; and economic considerations. Published by the UF Department of Wildlife Ecology and Conservation, May 2007.